2008
DOI: 10.1111/j.1582-4934.2008.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles in surgically‐induced carotid stenosis: a combined transcriptomic and proteomic investigation

Abstract: Vascular injury aimed at stenosis removal induces local reactions often leading to restenosis. The aim of this study was a concerted transcriptomic-proteomics analysis of molecular variations in a model of rat carotid arteriotomy, to dissect the molecular pathways triggered by vascular surgical injury and to identify new potential anti-restenosis targets. RNA and proteins extracted from inbred Wistar Kyoro (WKY) rat carotids harvested 4 hrs, 48 hrs and 7 days after arteriotomy were analysed by Affymetrix rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 44 publications
(60 reference statements)
6
35
0
Order By: Relevance
“…In addition, internal and external elastic lamina and media disruptions at the injury site were evident, often with media substitution by fibrotic tissue. Our previous gene expression microarray data obtained in this model [12] revealed the early and marked upregulation of inflammation-related genes, thus supporting the expected picture of inflammatory cell infiltration in the acute phase after arteriotomy (mainly at 4 h and 3 days after arteriotomy).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In addition, internal and external elastic lamina and media disruptions at the injury site were evident, often with media substitution by fibrotic tissue. Our previous gene expression microarray data obtained in this model [12] revealed the early and marked upregulation of inflammation-related genes, thus supporting the expected picture of inflammatory cell infiltration in the acute phase after arteriotomy (mainly at 4 h and 3 days after arteriotomy).…”
Section: Discussionsupporting
confidence: 59%
“…TLRs are known to link innate and adaptive immunity. The activation and the role of TLR2 and TLR4 in inflammation and neointima proliferation associated to stenosis progression after vascular injury has already been highlighted by other studies [12][13][14]. The decrease of mRNAs coding for TLR2 and TLR4 in injured carotids from MSC-treated rats in comparison to DMEM-treated rats (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Innovative strategies, e.g. based on local gene delivery, targeted inhibition of gene expression, or stem cell-mediated repair of injured vessels [36,37] have been successfully tested in animal models of vascular stenosis. Additional studies will be necessary to verify the effectiveness of these strategies also in patients.…”
Section: Polyamine Synthesis and Functionsmentioning
confidence: 99%
“…Microarraybased studies of gene expression in a rat model of carotid arteriotomy revealed that vascular injury induced an acutely increased expression of genes involved in the polyamine metabolic pathway, including ODC, SSAT, AdoMetDC and arginase I [36].…”
mentioning
confidence: 99%